Cysteine proteases in atherosclerosis. (9th March 2017) - Weiss‐Sadan, Tommy; Gotsman, Israel; Blum, Galia
Abstract : Atherosclerosis predisposes patients to cardiovascular diseases, such as myocardial infarction and stroke. Instigation of vascular injury is triggered by retention of lipids and inflammatory cells in the vascular endothelium. Whereas these vascular lesions develop in young adults and are mostly considered harmless, over time persistent inflammatory and remodeling processes will ultimately damage the arterial wall and cause a thrombotic event due to exposure of tissue factors into the lumen. Evidence from human tissues and preclinical animal models has clearly established the role of cathepsin cysteine proteases in the development and progression of vascular lesions. Hence, understanding the function of cathepsins in atherosclerosis is important for developing novel therapeutic strategies and advanced point of care diagnostics. In this review we will describe the roles of cysteine cathepsins in different cellular process that become dysfunctional in atherosclerosis, such as lipid metabolism, inflammation and apoptosis, and how they contribute to arterial remodeling and atherogenesis. Finally, we will explore new horizons in protease molecular imaging, which may potentially become a surrogate marker to identify future cardiovascular events. Abstract : The involvement of cysteine cathepsins in the pathology of cardiovascular diseases has been established across the board from animal models to humans. This has led to a deep interest in cathepsins as drug targets or surrogate markers for pathological arterial plaques. Recently, major breakthroughs in cardiovascular imaging modalities and targeted cathepsin–small molecule complexes have significantly advanced this approach into the clinical arena.